(untitled) (Research, Society and Development, 2021)
The new Coronavirus (COVID-19) constitutes a Public Health Emergency of International Importance - the highest level of alert by the World Health Organization. Nursing professionals have routinely faced precariousness in the work process and numerous problems in the health system. The aim of this study was to analyze the evidence from scientific publications about the challenges faced by nursing professionals in the face of the SARS-COV2 Coronavirus pandemic. The integrative review was used, in which 10 scientific articles made available in full, in the last 5 years, selected in the Virtual Health Library, comprised the analyzed sample. The results showed the challenges faced by nursing in the context of the pandemic context in question. As a result, it can be concluded that nursing professionals have always been challenged over time and with the arrival of the pandemic by the SARS-COV2 Coronavirus these challenges have taken on unimaginable proportions.